REAKSI PASAR MODAL INDONESIA TERHADAP PERISTIWA PENGUMUMAN PAKET KEBIJAKAN EKONOMI JILIJD II - Nurbaity Muzakir, Syarifah Rahmawati (Departemen Manajemen, 2017)
This research examines stock market reaction to the announcements economic policy package II. The variables used in this research are average abnormal return (AAR) and abnormal trading volume activity (ATVA). Analysis model in this research is event study which has 7 days window period (23 September - 2 October 2015). Hypothesis testing used are one sample t-test and paired sample t-test. Using purposive sampling, in this research there is 239 samples. The results of this research based one sample t test showed that the market reacts before the announcement economic policy package II, while at the event date, and after announcement economic policy package II, stock market did not react significantly. The results from the paired sample t test of the average abnormal return and the average abnormal trading volume activity shows that there is no significant difference before and after the event. From the results of this research concluded that the Indonesian capital market is efficient in semi-strong form. Keywords: Announcement of Economic Policy Package II, Stock Market Reaction, Efficient Market, Event Study, Average Abnormal Return, Average Abnormal Trading Volume